Splenopancreatectomy, laparoscopicapproach. Step-by-step surgery - Barboza Martínez, Alejandro; Soumastre, Alejandro; Irigoyen, Virginia; Espinosa, Gabriela; Massaferro, Gabriel (Cirugía del Uruguay, 2025)
Watch the video on YouTube https://www.youtube.com/watch?v=2Xwr8fhVsbU&t=5s Distal pancreaticresections (to the left of the superior mesenteric artery), whether due to benign or malignant causes, represent a significant proportion of pancreatic surgeries.1,6 They are necessary procedures when curative treatment of a malignant lesion in the body and/or tail of the pancreas is indicated (often requiring splenectomy).2 Laparoscopic surgery, as is well known, offers several advantages over open laparotomy; this approach has evolved over recent decades, with studies validating its oncological safety.3,4 This procedure requires, as in all surgeries, an in-depth knowledge of regional anatomy and advanced surgical expertise to perform it safely both technically and oncologically.5,7A video is presented below of a 60-year-old female patient with a malignant-appearing lesion in the body and tail of the pancreas, identified on MRI and CT, which also revealed two lesions corresponding to simple cysts in the left liver lobe. A distal splenopancreatectomy was performed through a fully laparoscopic approach, detailing the step-by-step surgical procedure and subsequent postoperative course. We highlight that, when defining the oncologic resection margin, it is considered positive (R1) when tumor cells are presentlessthan 1 mm from the resection edge.8,9 A macroscopic margingreater than 1.5 cm from the resection border is therefore considered sufficient. In our patient's case, the lesion was located in the pancreatic tail, and the proximal transection was performed at the level of the suprapancreatic splenic artery, posterior to its origin from the celiac trunk, after it was divided between clips; therefore, the margin clearly exceeded the required distance. The distal margin is also considered adequate, given that the spleen is included in the specimen. Finally, regarding lymph node dissection, peripancreatic nodes and those adjacent to the suprapancreatic splenic artery and splenic hilum corresponding to groups 10 and 11 of the Japanese surgical classification were removed.